PENGARUH DISIPLIN KERJA DAN LINGKUNGAN KERJA FISIK TERHADAP KINERJA KARYAWAN MELALUI MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING - MOHAMMAD BUKHORI; ERLYANA KUSUMA DEWI (AKADEMIKA, 2018)
Thisresearch istoknowthe influence ofwork discipline, physicalwork environmenttoemployee performance throughwork motivationasintervening variable ofproductionpartofPT.PertaminaEP Asset 5Field Sangasangaineast Kalimantan. Thisresearch wasconducted by surveymethodon77employeesofPT. PertaminaEPAsset5FieldSangasangainEastKalimantan.The result of analysis and discussion shows that: (1) work disciplinehasnegativeeffectonemployee'sperformance,(2) physicalwork environmenthaspositiveeffectonemployee'sperformance,(3) workdisciplinehas positiveeffectonworkmotivation,(4)thephysicalworkenvironmenthasapositive effectonworkmotivation,(5) work disciplinehasanegativeeffect onemployee performance, (6) work discipline has negative effect on employee performance throughworkmotivationasinterveningvariable,(7) physicalworkenvironment positively influenceto employeeperformance throughwork motivationasintervening variable.